2018
DOI: 10.1103/physrevlett.121.159901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Persistence-Driven Durotaxis: Generic, Directed Motility in Rigidity Gradients [Phys. Rev. Lett. 118 , 078103 (2017)]

Abstract: In deriving continuum equation (5) for the probability distribution Pðx; tÞ ¼ ρ þ ðx; tÞ þ ρ − ðx; tÞ from Eqs. (3) and (4) for the densities of left and right movers, we overlooked a term proportional to the difference between ρ − and ρ þ. As a result, Eq. (5) is incorrect. In the case that the cell velocity v c is uniformly constant, it should read

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…88 As a concrete manifestation, cells seeded on a substrate with a gradient of stiffness migrated from the soft towards the stiff side or aligned with the boundary to avoid the soft substrate. 89 In addition, cells on stiffer substrates exhibited more elongated and spread geometry. 90 Contact guidance is considered a symbol of recognition between cell morphology and matrix topographies.…”
Section: Topologymentioning
confidence: 99%
“…88 As a concrete manifestation, cells seeded on a substrate with a gradient of stiffness migrated from the soft towards the stiff side or aligned with the boundary to avoid the soft substrate. 89 In addition, cells on stiffer substrates exhibited more elongated and spread geometry. 90 Contact guidance is considered a symbol of recognition between cell morphology and matrix topographies.…”
Section: Topologymentioning
confidence: 99%
“…In order to study cell behaviors in microenvironment, a number of interesting works have been done in recently years. It was reported that the substrates with different rigidities lead to different cell movements, namely stiffer substrates generally promote the directionality of cell movement, while soft substrates typically result in random motions [10]. These distinct behaviors regulated by substrate stiffness are called as "durotaxis", which are combined with mechanical strains to control a number of pathological processes involving cell migration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Different from the cases above whose characteristics and properties are assumed to be non-varying with time, the more complex microenvironment changes globally or locally due to the changes of temperature, pressure, the heterogeneous surfaces in which cells migrate [10,11], the special components (oriented fibers) [14] or the concentration of biochemical factors [7] such as cytokine or drug molecules. In addition, migrating cells can actively remodel the microenvironment either mechanically or chemically, leading to spatial-temporally varying properties that in turn influences cell migration [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…39,[42][43][44] Cells can also exhibit directed motion in gradients of rigidity, which is called durotaxis, and has recently sparked renewed theoretical interest. [45][46][47][48] With regard to bacteria, mechanical modelling efforts have mostly focused on the understanding of pilus-based migration. 5,11,21,49,50 However, the role of substrate rigidity for bacterial migration has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%